The impact of change consultants’ dialogic mindset: towards a game-theoretic explanation - Makoto Nagaishi (Future Business Journal, 2023)
Abstract This study aims to provide a theoretical argument and examples supporting the author’s proposition that change consultants’ mindsets significantly impact resulting performances. While some scholars assert diagnostic and dialogic change processes can co-exist as complementary modes of engagement, the other stream of research postulates that (1) the diagnostic and dialogic “mindsets” rely on different behavioral assumptions and (2) the distinction between “methodologies” and “mindsets” is critical in analyzing whether the practices are diagnostic or dialogic. In the author’s preliminary game-theoretic settings, successful collective outcomes are highly probable with the dialogic mindset of change consultants, irrespective of the types of adopted methodologies. By contrast, dialogic methodologies in the later stage may not lead to successful collaboration if the change initiative started from the diagnostic interventions with a diagnostic mindset.